Financial Knowledge Moderating The Effect Of Money Attitude On Personal Financial Management Behavior Of Students - Dwi Kumalasari; Muhadjir Anwar (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Attitude towards money or what is often called money attitude is an individual's perception of money based on his state of mind. This study aims to determine the level of personal financial management of students which influenced by attitudes with financial knowledge as a moderation medium. The research method used in this study was a quantitative method. Undergraduate students of Management Study Program in the UPN "Veteran" Jawa Timur were chosen by the researcher to be the population of this study. The proportionate stratified random sampling method was chosen by the researcher as a sampling technique with 108 students was respondents. Distribution of questionnaires is a data collection method used in this study. Data analysis and processing techniques used Partial Least Square (PLS) with WarpPLS 7.0 software. which produces information that money attitude had a significant effect on personal financial management behavior and also proves that financial knowledge is able to moderate the effect of these two variables.